Isolation and characterization of endophytic fungi and their antagonistic activity against Fusarium spp., the causal agent of yellow disease in Piper nigrum - SOFIAN SOFIAN; SUYADI SUYADI; NURHASANAH NURHASANAH; SOPIALENA SOPIALENA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Sofian, Suyadi, Nurhasanah, Sopialena. 2025. Isolation and characterization of endophytic fungi and their antagonistic activity against Fusarium spp., the causal agent of yellow disease in Piper nigrum. Biodiversitas 26: 1816-1826. Yellow disease in pepper (Piper nigrum), caused by Fusarium spp., significantly impacts crop productivity, manifesting as yellowing, wilting, defoliation, and root necrosis. Endophytic fungi offer a sustainable alternative to chemical pesticides for managing Fusarium spp. infections. The objective of this study was isolate and characterize endophytic fungi from Piper nigrum, Piper crocatum, and Capsicum annuum. Fungi were obtained from roots, stems, and leaves, cultured on PDA medium, and identified based on macroscopic and microscopic traits. The result revealed that a diverse community of endophytic fungi was associated with host-specific variations in fungal taxa. P. nigrum exhibited the highest fungal diversity, likely due to its rich phytochemical composition. A total of six fungal genera were identified: Trichoderma sp., Gliocladium sp., Penicillium sp., Aspergillus sp., Geotrichum sp., and Cephalosporium sp., each displaying unique morphological and functional attributes. Penicillium sp., Gliocladium sp., and Trichoderma sp. were found in several host plants, demonstrating their adaptability and potential for pathogen suppression. Notably, Gliocladium sp. and Trichoderma sp. showed remarkably rapid growth, giving them an advantage in competing for space and resources. Antagonistic assays further confirmed their ability to inhibit Fusarium sp.; Gliocladium sp. isolated from P. nigrum exhibited the highest effectiveness, consistently outperforming other isolates. This remarkable performance may be attributed to its dual antagonistic strategies—competition and antibiosis. Gliocladium sp. (PN) demonstrates a remarkable ability to establish sustained interactions with pathogens, ensuring prolonged suppression of Fusarium sp. over time. This capability highlights its potential utility in managing yellow disease in P. nigrum.